Differentiation of Human GBM From Non-GBM Brain Tissue With Polarization Imaging Technique - Liu, Yi-Rong; He, Hong-Hui; Wu, Jian (Frontiers in Oncology, 2022)
Glioma is a kind of malignant primary brain tumor with high recurrence rate because it’s difficult to be completely resected surgically, and several imaging methods have been used in clinical to detect the glioma with its residual. The propose of this research is to characterize different microstructural information and optical properties of formalin soaked unstained glioblastoma (GBM) and non-GBM tissue with polarization imaging technique (PIT), and provide a novel method to detect GBM during surgery. In this paper, 3×3 Mueller matrix polarization experimental system in backscattering mode was built to detect the GBM and non-GBM tissue bulk. The Mueller matrix decomposition and transformation parameters of GBM and non-GBM tissue were calculated and analyzed, shown that parameter (1-Δ) and t are good indicators for distinguishing GBM from non-GBM tissues. Furthermore, the Central Moment Coefficients (CMCs) of Frequency Distribution Histogram (FDH) were also calculated and used to distinguish the cancerous tissues. The results of the experiments confirmed the feasibility of PIT applying in the clinical to detect glioma, laying the foundation for the subsequent non-invasive, non-staining glioma detection.